OYSTER MUSHROOM WASTE AS MANURE IN FISH CULTURE A PRELIMINARY STUDY - DUBE, KIRAN; DWIVEDI, ALKESH (Journal of Indian Fisheries Association, 2015)
In an atte1npt to recycle the waste substrates of the oyster-1nushroon1crop, tanlis were stocked with seed of Indian n1ajor carp Cirrhinusm .. rigala at the rate of 600,000/ha and waste substrate was applied atweekly interval at 0,50,100~150;200 and 250 g/tank Oyster mushromn wastenot only provided highly nutritive colonised detritus to the fish as directfeed, but also produced rich planltton in the tanl{, In waste treated tanli;:s,production was better than in the control in 150, 200 and ~50 g/tanl{treatment suggesting the possibility of fish p oyster m.ushromn integÂ·ration.